Examination of Metabolic Syndrome Knowledge and Awareness Levels of Individuals Going to Fitness Centers - Kavuran, Korhan; Yıldırak, Ahmethan; Erdoğan, Ramazan (Journal of Neonatal Surgery, 2025)
Metabolic syndrome is defined as a condition that includes a number of health problems such as insulin resistance, hypertension, obesity and dyslipidemia and increases the risk of heart disease, stroke and type 2 diabetes, and poses a serious threat to public health. Therefore, it is widely accepted that physical activity and regular exercise are effective in preventing metabolic syndrome. This research aims to examine the metabolic syndrome knowledge and awareness levels of individuals attending fitness centers in terms of variables such as gender, age, height, weight, weekly exercise frequency and monthly income. 189 volunteers (138 women, 51 men) who regularly go to fitness and health centers participated in the study. "Personal Information Form" was used to collect demographic information of the participants and "Metabolic Syndrome Awareness Scale" was used to measure metabolic syndrome awareness levels. In the analysis of the data, the relationships between demographic characteristics and awareness level were evaluated by using the SPSS statistical package program. According to the research results, it was determined that gender, age, body weight, weekly exercise frequency and monthly income variables created a significant difference on the metabolic syndrome awareness level. It was found that female participants' metabolic syndrome awareness levels were higher than men. Additionally, it was determined that the metabolic syndrome awareness levels of individuals who exercise regularly at least three days a week were significantly higher than other individuals. As a result, it was observed that the metabolic syndrome knowledge and awareness levels of individuals attending fitness centers were generally at a medium level. These findings point to the need to disseminate health education programs and awareness campaigns in order to increase awareness about metabolic syndrome in society. It is thought that such programs will contribute to individuals understanding the risk factors associated with metabolic syndrome, adopting healthy living habits and thus living a better quality of life.